Effect of Cavity Losses on Atomic-squeezed States Produced via Time-varying Cavity Frequency (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2021)
We investigate the effect of cavity losses on squeezed-spin states generated via two-photon character of the field for a Bose-Einstein Condensate embedded within the Fabry-Perot optical cavity with a moving mirror for the initial vacuum cavity field. We further show how cavity decay acts as an additional factor in controlling the spin-squeezing.
Keywords: Bose-Einstein condensates; Optomechanical cavity; Squeezed states